Trends of Agency Theory in Accounting, Financial and Management Research: Systematic Literature Review - Bambang Susilo; Ria Ria (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to present publications trends of Agency theory in accounting, financial and management research from the Scopus database using bibliometric analysis. This research used Publish or Perish by Harzing for citations in the form of metrics, Microsoft Excel for frequency analysis and VOS viewer for visualization of data. Based on the results of research, the publications trends of Agency theory in accounting, financial and management research have been consistently increasing since 2021 with 21 articles. The most popular keywords identified in the document set are: case study, corporate performance, influence, research, theory, effect, financial performance, relationship, study, earning management, earning quality, firm, quality, audit committee, evidence, Indonesia and management, case, company, investigation and Malaysia. This research is one of the researches that examine the publication of Signaling Theory in Accounting based on the Scopus science database using Harzing’s Publish or Perish.